2017
DOI: 10.1016/j.jcrs.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery practices in the United States Veterans Health Administration

Abstract: The survey results indicate that in cataract surgery in the VHA, routine preoperative testing is commonly performed and emerging practices, such as femtosecond laser-assisted cataract surgery and immediate sequential bilateral cataract surgery, have limited roles. The results of this survey could benchmark future trends in U.S. cataract surgery practices, especially in teaching hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Only 5% of the respondents in this survey performed FLACS, which showed that FLACS still had a limited role in the Republic of Korea. Possible explanations include the high cost of purchase and operation, as well as the lack of clear advantages of FLACS over traditional phacoemulsification [111213]. According to the 2018 American Society of Cataract and Refractive Surgery clinical survey, only an average of 8% of cataract patients were treated using FLACS.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5% of the respondents in this survey performed FLACS, which showed that FLACS still had a limited role in the Republic of Korea. Possible explanations include the high cost of purchase and operation, as well as the lack of clear advantages of FLACS over traditional phacoemulsification [111213]. According to the 2018 American Society of Cataract and Refractive Surgery clinical survey, only an average of 8% of cataract patients were treated using FLACS.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite the significant potential impact of evolving sedation practices on cataract surgery in the Veterans Health Administration (VHA), literature on sedation use in resident performed cataract surgery at the VHA is sparse. 5 …”
Section: Introductionmentioning
confidence: 99%